Back to basics: How young mothers learn about sex and sexuality - Dudley, James; Crowder, Amanda; Montgomery, Tchernavia R. R. (Sex Education : Sexuality, Society and Learning, 2014)
Adolescent pregnancy continues to be a major concern for policy-makers, programme developers, helping professionals and society generally in the USA, especially in light of the US federal government's legislative emphasis on abstinence-only sex education until recently. Studies have found that abstinence-only programmes do not succeed in preventing young people from becoming sexually active or pregnant; most young people have sexual intercourse in their teenage years long before they even contemplate marriage. The purpose of this qualitative study was to explore how 32 teenage mothers learned about sex and their related views about pregnancy and birth control. Findings indicate that they have often received little accurate information about sex from their parents and schools. Findings also reveal their widely varying views about birth control and pregnancy. Overall, the findings support the need for comprehensive sexuality education that addresses the topics covered in this study in an age-appropriate manner. The findings also suggest ways that helping professionals in other settings besides schools can help young people address these issues.
Keywords: 2000 à aujourd'hui; 2010-2019; Infections transmisibles sexuellement et par le sang; adolescentes*; amériques; contraception; discipline; maternité; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sexualité; thématiques; travail social; éducation sexuelle; états-unis; étude qualitative